Fever of Unknown Origin, Wasting Syndrome and Bone Marrow Involvement: A Leprosy Case Report - Santana, Marcela Araujo de Oliveira; da Costa, Willian Vargas Tenório; Celestino, Isadora Costa; dos Santos, Diogo Fernandes; Dornelas, Bruno de Carvalho; Pavelka, Matthew Martin; Luppi, Andrea De Martino; Goulart, Isabela Maria Bernardes (Frontiers in Immunology, 2022)
Mycobacterium leprae, the etiologic agent of leprosy, is an acid-fast-staining and slow-growing bacilli that infect macrophages and Schwann cells individually or through forming globi. The clinical presentation of leprosy is broad and depends on the host immune response. We report a case of a 42-year-old Brazilian man presenting with fever of unknown origin (FUO), anemia, wasting syndrome, and neuropathy. The diagnosis of lepromatous leprosy was made after an extensive investigation revealed the presence of M. leprae in the bone marrow. Bone marrow involvement in leprosy is rare and some authors believe the presence of M. leprae in the bone marrow can act as a reservoir of the disease facilitating future relapses. It is important to investigate bone marrow involvement in leprosy, especially when the patient presents with cytopenias and positive epidemiologic history.